2022
DOI: 10.1021/acs.inorgchem.2c01442
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Synergy: Aurophilicity and Aryl Stacking in Bis(gold(I)aryl)-dmpm Complexes

Abstract: Bis(dimethylphosphino)methane (dmpm) was used as a ligand to synthesize four semi-supported dinuclear gold(I) complexes, dmpm(AuR) 2 (R = Cl, C 6 H 5 , C 6 Cl 5 , and C 6 F 5 ), which were studied concerning the synergistic effects of two weak noncovalent interactions: aurophilic and aryl−aryl stacking interactions. The chloro-substituted complex was synthesized by the ligand substitution of (tht)AuCl with dmpm and further functionalized by the reaction with PhMgBr or in situ-generated C 6 Cl 5 Li to afford th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…By recognizing certain structural elements as particularly suited to form strong LDF, such as pentachlorophenyl groups, they can be used to construct noncovalent synergies, e.g., by combining aryl stacking with aurophilic interactions to enhance the latter for optimizing photoluminescence properties. 44 In combination with other WNCIs, such as dative, halogen, or chalcogen bonds, LDF contribute to an overall stabilization. Their effects are partially compensated for in solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By recognizing certain structural elements as particularly suited to form strong LDF, such as pentachlorophenyl groups, they can be used to construct noncovalent synergies, e.g., by combining aryl stacking with aurophilic interactions to enhance the latter for optimizing photoluminescence properties. 44 In combination with other WNCIs, such as dative, halogen, or chalcogen bonds, LDF contribute to an overall stabilization. Their effects are partially compensated for in solution.…”
Section: Discussionmentioning
confidence: 99%
“…By recognizing certain structural elements as particularly suited to form strong LDF, such as pentachlorophenyl groups, they can be used to construct noncovalent synergies, e.g., by combining aryl stacking with aurophilic interactions to enhance the latter for optimizing photoluminescence properties …”
Section: Discussionmentioning
confidence: 99%
“…These unusually strong dispersion interactions are a result of the strong relativistic effects exerted by the gold atom. Thus, there is an abundance of examples of Au­(I) compounds, whose arrangement in the solid state appears to be governed by aurophilicity. ,, Furthermore, it has been found that these attractive interactions are not limited to Au­(I), but can also be found for other ions with closed-shell configuration, which is why they are commonly referred to as “closed-shell interactions”. Because relativistic effects are most pronounced in gold, it also exhibits the strongest attractive forces, reaching values up to those of hydrogen bonds. Metallophilic bonding of other closed-shell ions is much weaker.…”
Section: Introductionmentioning
confidence: 99%